Prevalence of Rose Powdery Mildew in Different Districts of Himachal Pradesh, India - Vijay Kumar; Sunita Chandel (International Journal of Fungi, 2024)
The present investigation was done in the month of March to June and August to November to survey the powdery mildew infection on commercial greenhouses, nurseries and garden grown roses. Powdery mildew manifests as white to grayish patches of powdery growth on the surfaces of plant organs. Powdery mildew of rose was presented all rose growing areas of districts Bilaspur, Kangra, Mandi, Sirmour, Shimla and Solan during the years 2015 and 2016 in moderate to severe. Rose powdery mildew cause decreased the quality and quantity of the rose stem production as well as loose flowers yield. The average range of disease incidence and per cent disease index varied between 48.50 to 66.75 and 22.22 to 36.02, respectively. The present study examined the prevalence of powdery mildew disease in roses grown in orchards and commercial stands between March, June, August and November, Powdery mildew on roses is characterized by the growth of white-gray powdery spots or patches on the back of the plant parts This study found that in 2015 and 2016 in rose growing areas of Bilaspur, Kangra , Mandi, Sirmoor, Shimla and Solan districts were all prevalent with powdery mildew , with infestation levels ranging from moderate to severe. The disease has a severe impact on the rose tree, reducing the number and quality of rose trees and reducing the production of soft flowers. humanize text % disease index and disease level ranged from 22.22 to 36.02 to 48.50 to 66.75, respectively. These high rates indicate that powdery mildew is a major constraint in rose growing in these areas, and that effective management strategies are needed to minimize its impact.
Keywords: Powdery mildew; disease incidence; disease index; rose